The need for construction court in Nigeria : a case study of UK and Malaysia / Barakat Adebisi Raji - Raji, Barakat Adebisi (Universiti Teknologi MARA, 2020)
This paper discusses the delay in construction disputes and the need for construction courts for speedy resolution. The inadvertent delay occasioned in court on construction dispute cases has resulted in loss of time, cost and quality of projects. This has also resulted into loss of jobs, unemployment, bankruptcy, ahd loss of lives and property. This has accounted for series of unnecessary adjournments of construction cases in courts. It is pertinent that construction contracts are awarded with specificity in relation to time of completion. Hence, when issues that need to be tackled arise, there is the need for a special court with specialist in construction to address the problem without causing undue delay which usually resulted in abandonment of projects. This paper therefore advocates for the establishment of construction court for prompt dispensation of construction cases to enable fast delivery of projects and quality performance of contractors.